Nanobiotechnology-Modified Cellular and Molecular Therapy as a Novel Approach for Autoimmune Diabetes Management - Lawand, Priyanka V.; Desai, Shivani (Pharmaceutical Nanotechnology, 2022)
Several cellular and molecular therapies such as stem cell therapy, cell replacement therapy, gene modification therapy, and tolerance induction therapy have been researched to procure a permanent cure for Type 1 Diabetes. However, due to the induction of undesirable side effects, their clinical utility is questionable. These anti-diabetic therapies can be modified with nanotechnological tools for reducing adverse effects by selectively targeting genes and/or receptors involved directly or indirectly in diabetes pathogenesis, such as the glucagon-like peptide 1 receptor, epidermal growth factor receptor, human leukocyte antigen (HLA) gene, miRNA gene and hepatocyte growth factor (HGF) gene. This paper will review the utilities of nanotechnology in stem cell therapy, cell replacement therapy, beta-cell proliferation strategies, immune tolerance induction strategies, and gene therapy for type 1 diabetes management.
Keywords: type 1 diabetes